2020
DOI: 10.4103/jpbs.jpbs_57_20
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of orthopantamogram in lower third molar surgery: Inter- and intra-observer agreement

Abstract: A BSTRACT Context: The evaluation of relationship between the roots of impacted lower third molar (IL3M) and inferior alveolar nerve injury (IAN) with orthopantamogram (OPG) is mandatory before performing de-impaction surgery. An investigation is considered reliable if it can be reproduced by various examiners. Assessment of OPG is subjective and varies among examiners. OPG is reliable to clinicians if the interpretation is not a product of guess work. Aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Orthopantamograms (OPGs) have historically been used as a standardized evaluation technique to evaluate and arrange this surgical removal 14 . OPG is a common investigation to investigate to see how an impacted tooth relates with the mandible 15 . OPG remains among the most effective diagnostic methods for determining impacted lower third molar, according to reports.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Orthopantamograms (OPGs) have historically been used as a standardized evaluation technique to evaluate and arrange this surgical removal 14 . OPG is a common investigation to investigate to see how an impacted tooth relates with the mandible 15 . OPG remains among the most effective diagnostic methods for determining impacted lower third molar, according to reports.…”
Section: Discussionmentioning
confidence: 99%
“…There are still many people who employ the Rood and Shehab criterion, that focus on traditional radiographs 16 . There are differences in how different surgeons as well as other specialists understand the OPG 15 . Prabakaran conducted a survey to see whether oral radiologists & oral surgeons coincide when it comes to assessing the close nerve root relationships in OPG, which are regarded as warning indications 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Sureshkannan P suggested that For such above indications in OPG, there was good inter-observer concordance and moderate to great intra-observer confidence for both operators. The assessment of the OPG for the aforementioned symptoms is generally accepted by the specialists and aids in determining the potential danger of nerve damage prior to surgery 10 . This could be ascribed to variations in how each observer saw the relationships between the nerve roots, the calibre of the OPG, and additional susceptibility variables like age, sex, as well as root curve.…”
Section: Introductionmentioning
confidence: 99%